Peranan Motivasi dan Disiplin Kerja terhadap Produktivitas Kerja Pegawai Pada Perusahaan Daerah Air Minum (PDAM) Kota Sukabumi - Untung Margono (LP2M CBI PRESS, 2020)
Human resources need to be given motivation and work discipline towards work productivity, motivation regarding human behavior, and an important element in management and it cannot be denied that one of the main motivations for a person to become an organizational human being is, to be able to fulfill his needs, motivation and work discipline by the company. it turns out to be able to increase work productivity, this is proven by the results of statistical calculations. The research methodology is used through direct and indirect data collection methods and analysis through quantitative calculation methods and quantitative descriptive